ACHIEVEMENT OF BIOLOGY USING QUESTION STUDENT HAVE ACTIVE LEARNING OBSERVED FROM LEARNING ACTIVITY OF STUDENT’S ON XI IPA GRADE OF SMA NEGERI 1 SUKOHARJO - Rahayu, Eni; Rosyidi, Alvi; Indrowati, Meti (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT ? The purposes of this research were to know: 1) the influence of learning strategy toward achievement biology of student?s on XI IPA grade of SMA N 1 Sukoharjo ; 2) the influence of student?s learning activity toward achievement biology of student?s on XI IPA grade of SMA N 1 Sukoharjo ; 3) the interaction between learning strategy and student?s learning activity toward achievement biology of student?s on XI IPA grade of SMA N 1 Sukoharjo and; 4) the influence of the combined effects between of learning strategy and student?s learning activity which better of student?s on XI IPA grade of SMA N 1 Sukoharjo This research was a quasi experiment research with Randomized Control Only Design. Learning strategy and student?s learning activity were independent variables and student?s achievement of study biology was the dependent variable. The population of this research was all of student?s on Xl lPA grade of SMAN 1 Sukoharjo. The samples of this research were the student?s of class Xl IPA 4 as the control class and student?s of class XI IPA 3 as the experimental class. The sample of this research was established by Cluster Random Sampling. The techniques for collecting data were had test, questionnaire, and observation. The data were analyzed by anava two away in different cell and then continued test anova with test LSD to understand treatment influence step. The conclusion of this research were: 1) the learning strategy had significant influence toward achievement biology in cognitive, affective and pshycomotor domain of student?s on XI IPA grade of SMA N 1 Sukoharjo ; 2) the student?s learning activity had significant influence toward achievement of biology in pshycomotor but didn?t have significant influence in cognitive and afective domain of student?s on XI IPA grade of SMA N 1 Sukoharjo; 3) there wasn?t interaction between learning strategy and student?s learning activity toward achievement of biologi cognitive, affective and pshycomotor domain of student?s on XI IPA grade of SMA N 1 Sukoharjo and ; 4) on the strength of continued test have been obtained results that significant influence the effect of the combination between of learning strategy and learning activity which the achievemenant biology of higher with the use of active learning Student Question Have observed from the high student?s learning activity in cognitive, affective and psychomotor domain of student?s on XI IPA grade of SMA N 1 Sukoharjo. Keywords : achievement, biology, question student have, active learning, learning Activity